Liquid Metal-Tunable Miniaturized Bimodal Cavity for Enhanced Measurement Accuracy in the Ism Bands - Karatay, Anil; Yaman, Fatih; Yaman, Fatih (Ieee-inst Electrical Electronics Engineers inc, 2024)
Enhancing measurement accuracy or reducing the effect of the neighboring modes in resonant cavities may necessitate the separation of mode frequencies. However, in ISM-band measurement configurations utilizing a rectangular or cylindrical cavity, the placement of the first two modes at 2.45 and 5.8 GHz is unattainable, necessitating the presence of additional modes in between that would potentially degrade measurement accuracy. This article begins with an analytical approach, employing Lagrange multipliers for the first time to reveal the level of separation achievable in the frequency domain between the initial two modes within these types of conventional cavities. The analytical results were also verified with a numerical grid search. Subsequently, innovative strategies have been introduced to surpass this intrinsic constraint that reduces the measurement accuracy in various applications. A novel miniaturized cavity configuration has been proposed to operate bimodally at 2.45 and 5.8 GHz and manufactured with a 3-D printer. It has been ensured that there are no physical modes present in between, and measurements of the structure have been conducted. Another notable innovation of the article is the capability of tuning the proposed cavity structure by means of liquid metal displacement. Thus, a more flexible tuning method compared to mechanical tuning techniques can be achieved, enabling precise adjustment of the desired measurement frequency. Good agreement between the simulation and measurement results has been reported.
Karatay, Anil/0000-0002-4516-3028; Yaman, Fatih/0000-0002-4745-9957
Keywords: Resonant frequency; Permittivity measurement; Mathematical models; Liquids; Microwave measurement; Microwave integrated circuits; Microwave FET integrated circuits; Additive manufacturing; analytical and numerical methods; enhanced accuracy; liquid metal; microwave cavities